Flatland: Rapid Prototyping of Distributed Internet Applications - Chesley, Harry; Kimberly, Greg; Drucker, Steven; Gupta, Anoop; White, Steve (2001)
Computer intra- and internets are widely used for client-server application such as web browsers. With the exception of e-mail, however, the same networks are seldom used for distributed, client-client or client-server-client applications. Such applications are difficult to develop and debug, and require a supporting infrastructure that is not readily available from existing systems. Flatland is a rapid prototyping environment that provides the underlying infrastructure and makes it easy to create and debug distributed internet application prototypes. In addition to the infrastructure needed for a distributed application, Flatland includes safe implementations of the most common sources of distributed application bugs – asynchronous operation and updating. Flatland also supports streaming audio-video and down-level clients.